2019
DOI: 10.1038/s41431-019-0501-7
|View full text |Cite
|
Sign up to set email alerts
|

Copy number variants in lipid metabolism genes are associated with gallstones disease in men

Abstract: Gallstones Disease (GSD) is one of the most common digestive diseases requiring hospitalization and surgical procedures in the world. GSD has a high prevalence in populations with European or Amerindian ancestry (10-20%) and the influence of genetic factors is broadly acknowledged. However, known genetic variants do not entirely explain the disease heritability suggesting that additional genetic variants remain to be identified. Here, we examined the association of copy number variants (CNVs) with GSD in a sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…In particular, CNV genotyping was crucial in studies involving diseases such as schizophrenia [ 216 , 217 ], bipolar disorder [ 216 ], Parkinson’s disease [ 218 ], Autism Spectrum Disorder [ 219 ] and attention deficit hyperactivity disorder [ 220 ]. Other CNVs studies included different outcomes such as HBV [ 221 , 222 ], autophagy [ 223 ], gallstones disease [ 224 ], vesicoureteral reflux [ 225 ], esotropia [ 226 ], cheap screenings for primary immunodeficiency [ 227 ] and COVID-19 potential targets [ 228 ]. For these studies, PennCNV was the most popular, followed by Nexus Copy Number, Birdsuite and QuantiSNP.…”
Section: Recent Studies Applying Inference Methods Of Snp Datamentioning
confidence: 99%
“…In particular, CNV genotyping was crucial in studies involving diseases such as schizophrenia [ 216 , 217 ], bipolar disorder [ 216 ], Parkinson’s disease [ 218 ], Autism Spectrum Disorder [ 219 ] and attention deficit hyperactivity disorder [ 220 ]. Other CNVs studies included different outcomes such as HBV [ 221 , 222 ], autophagy [ 223 ], gallstones disease [ 224 ], vesicoureteral reflux [ 225 ], esotropia [ 226 ], cheap screenings for primary immunodeficiency [ 227 ] and COVID-19 potential targets [ 228 ]. For these studies, PennCNV was the most popular, followed by Nexus Copy Number, Birdsuite and QuantiSNP.…”
Section: Recent Studies Applying Inference Methods Of Snp Datamentioning
confidence: 99%
“…Genetic variation of UGT1A genes has been associated with disorders of bilirubin metabolism including Gilbert's syndrome by multiple previous SNP GWAS studies (120,121) with, for example, very strong association signal at UGT1A10 for the intron variant rs6742078 (2_233763993_G_T) (122). This specific SNP has also been linked to other lipid metabolism disorders such as Gallstones Disease (GSD) (123) and although studies looking at CNV burden analysis of lipid metabolism genes has shown a significant enrichment in GSD cases none of those associations could be attributed to any single gene (124). Here we provide novel CNV associations at UGT1A genes with a direct link to bilirubin metabolism that could be an important risk factor for lipid metabolism related disorders.…”
Section: First Occurrences Icd10 Code Copy Number Variation Associationsmentioning
confidence: 99%
“…The cholesterol gallstone is the most familiar type of GD in cholecystectomy [ 2 ]. The prevalence of GD is extremely high in Western countries with the rate of about 10~20% [ 3 ]. Nowadays, GD has become more and more prevalent in China, ranging from 10 to 15% [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…(2) The functions of differential gut microbiota in GD patients. (3) The relationship between intestinal microbiota and traditional biochemical markers in patients with cholelithiasis. (4) The potential mechanism of how the intestinal microbial community affects the formation of gallstones.…”
Section: Introductionmentioning
confidence: 99%